Mapping innovation in the construction sector: A study of national firms in Malaysia / Chang Yean Fang - Chang, Yean Fang (2012)

(untitled)
Existing innovation in construction researches that mainly draw from manufacturing models and adopt a single dimension view of the firm or an institutional approach are limited due to the complexity of the construction sector and the nature of the innovation system that require it to be studied as a whole. Using a qualitative and inductive approach, this case study of four construction firms adopted the service sector adaptation of the Sectoral System of Innovation (SSI) framework to explain how the complex interactions, project-based nature and specific processes of construction influence construction innovation. The research questions asked what are the active components of a construction innovation system, how do institutions regulate the conduct of actors in the construction industry, and how do organizations connect institutions and firms to support innovation in the construction industry? The researcher found that innovation in construction is largely incremental and not revolutionary, typical of Schumpeterian Mark 1 systems. Construction firms are motivated to innovate for problem-centric or opportunity-centric reasons, as do firms in the service sector. Leadership is a strong determinant of innovation. Because construction involves multiple actors, innovation in construction is also a team effort that requires high levels of interaction and interdependency. In contrast to the manufacturing sector, informal forms of knowledge base and learning are considered more effective than formal systems and training. Clients provide direct or indirect input to innovation, depending on the construction subsector. Institutions regulate actors’ conduct in the construction innovation system (CIS) acting as both positive influences on and impediments to innovation. Meso-organizations play an intermediary role to institutions. Government does not play a strong role, but has the potential to play a supporting role by encouraging innovation. The CIS mapping from this research provides new knowledge to guide policy makers and the owners and managers of construction firms to increase iv innovation in construction. Theoretically, it extends the service sector adaptation of the SSI framework by developing a CIS framework as well as providing an integrated understanding of the characteristics of a construction innovation system to address the limitations of extant construction innovation literature.